GENOTOXIC ASSESSMENT OF Oreochromis niloticus and Coptodon guineensis ISOLATED FROM TWO HEAVY METAL CONTAMINATED RIVERS IN LAGOS STATE - ADEBESIN, O.A; IGWE, J.C.; MARTINS, V.N.; EJUETUEYIN, O.E.; ADESUYI, O.O.; MOKOLO, N.N. (Nigerian Journal of Fisheries, 2024)
Accumulation of heavy metals in water bodies contaminated by industrial effluents directly or indirectly poses health risk to both aquatic organisms and humans, culminating in genetic disorders and various organ diseases. This study was conducted across three locations in Lagos State, Nigeria: Maya River, Erikorodo, Ikorodu, Osborne Foreshore Lagoon, Ikoyi and a fish farm at the Nigerian Institute for Oceanography and Marine Research (NIOMR), Badore. Genotoxic assessment of the flesh and histopathology of the liver samples harvested from Oreochromis niloticus and Coptodon guineensis collected from the study sites were undertaken and physicochemical analyses of the water and sediment samples were conducted using atomic absorption spectrophotometer. Results showed that olive tail moment for wild Oreochromis niloticus from Maya River and wild Coptodon guineensis from Osborne foreshore lagoon was 13.50 and 5.54 respectively compared to 4.6 and 5.32 of the same species from the farm. ANOVA showed statistical significance in DNA damage, with p-values 0.012 for Oreochromis niloticus. High concentrations of Iron and Zinc, along with the highest levels of heavy metals, were detected in Maya River which suggests that aquatic animals sourced from these sites may pose health challenges if consumed.